2015
DOI: 10.4161/15592324.2014.993291
|View full text |Cite
|
Sign up to set email alerts
|

Repression ofAS2by WOX family transcription factors is required for leaf development in Medicago and Arabidopsis

Abstract: WOX transcription factors are key regulators of meristematic activity in plants. The Medicago WOX gene, STF, functions in maintenance of leaf marginal meristem, analogous to the function of WUS in the shoot apical meristem. Both STF and WUS directly repress AS2 expression in their respective domains. Ectopic expression of AS2 with WUS promoter leads to a narrow leaf phenotype and other phenotypes similar to the wus mutant. We also found that a wox1 prs wus triple mutant produces much narrower leaf blades than … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 36 publications
0
12
0
Order By: Relevance
“…Given the adaxial–abaxial patterning defects in wox1 prs mutants, WOX1 and PRS are likely involved in feedback regulation of adaxial–abaxial patterning factors at later stages of development. Among the adaxial patterning factors, WOX1/PRS promote the expression of HD-ZIPIII genes in the developing leaf margins, likely in part through inhibition of miR165/166 (Figure 3A) [84] WOX1/PRS also repress the expression of AS2 , restricting its expression to the adaxial domain of the leaf margin [87,88]. Meanwhile, WOX1/PRS influence the expression of abaxial-specific genes as well.…”
Section: The Coordination Of Adaxial–abaxial and Mediolateral Pattmentioning
confidence: 99%
“…Given the adaxial–abaxial patterning defects in wox1 prs mutants, WOX1 and PRS are likely involved in feedback regulation of adaxial–abaxial patterning factors at later stages of development. Among the adaxial patterning factors, WOX1/PRS promote the expression of HD-ZIPIII genes in the developing leaf margins, likely in part through inhibition of miR165/166 (Figure 3A) [84] WOX1/PRS also repress the expression of AS2 , restricting its expression to the adaxial domain of the leaf margin [87,88]. Meanwhile, WOX1/PRS influence the expression of abaxial-specific genes as well.…”
Section: The Coordination Of Adaxial–abaxial and Mediolateral Pattmentioning
confidence: 99%
“…It is even likely that WUS has a redundant function in leaf blade development with other WOX genes. The wox1 prs wus triple mutant exhibits a noticeably narrower leaf blade compared with the wox1 prs double mutant, implicating that WUS might function in regulating leaf lateral blade outgrowth in Arabidopsis (Zhang and Tadege, 2015), although this has not been investigated in detail. However, in M. truncatula , the mutation of HDL results in clearly altered leaf shape, changing from a more or less oval shape in R108 to heart-shaped blades in the mutant, suggesting that HDL may regulate leaf development in the proximal–distal axis in contrast to the role of STF in regulating blade outgrowth in the medial–lateral axis.…”
Section: Discussionmentioning
confidence: 99%
“…It was reported recently that leaf polarity genes are regulated by auxin in the primordium (Caggiano et al ). The WOX genes are also known to regulate the expression of both adaxially and abaxially expressed transcription factors and miRNAs (Nakata et al ; Zhang et al ; Zhang and Tadege ). Several WOX genes carry auxin responsive elements (Figure ), and a recent report showed that several auxin responsive factors directly regulate the WOX genes (Guan et al ).…”
Section: Leaf Margins Middle Domain and Adaxial‐abaxial Polaritymentioning
confidence: 99%